2021
DOI: 10.1016/j.asmart.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of an anatomical variation of bilateral long head of the biceps brachii tendons identified within the substance of bifid subscapularis tendons

Abstract: The long head of the biceps tendon is stabilized in the intertubercular groove by several anatomical structures. Dislocation or identification of the biceps tendon into or within the subscapularis tendon is very rarely mentioned in the literature. This is the first reported case of bilateral identification of the long head of the biceps tendons within the lateral subscapularis tendon. This report presents the case of a 51-year-old male patient who presented for bilateral shoulder pain. After failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, other authors have maintained that isolated dislocation of the LHBT might occur without rotator cuff injury. Ayoubi et al [ 17 ] reported on a case of bilateral dislocation without detection of any subscapularis tears. The patient’s symptoms were remarkably similar to those of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have maintained that isolated dislocation of the LHBT might occur without rotator cuff injury. Ayoubi et al [ 17 ] reported on a case of bilateral dislocation without detection of any subscapularis tears. The patient’s symptoms were remarkably similar to those of our patient.…”
Section: Discussionmentioning
confidence: 99%